Factors contributing to the uptake and maintenance of regular exercise behaviour in emerging adults. (March 2017) - Langdon, Jody; Johnson, Chad; Melton, Bridget
Objective: To identify the influence of parental autonomy support, basic need satisfaction and motivation on emerging adults' physical activity level and exercise behaviours. Design: Cross-sectional survey. Setting: This study convenience-sampled approximately 435 college students identified as emerging adults – aged 18–25 years, who did not have a child, own a home, or have sufficient income to be fully independent. Methods: Survey responses were used in a path model to investigate how parental autonomy support, psychological mediators and motivational processes influenced emerging adults' exercise behaviour. Results: The hypothesised model was supported with minor modifications. Most notable was the influence of parental physical activity level and autonomy support on psychological mediators, motivational processes and exercise behaviour. Conclusion: Results indicate that parents influence their children both directly and indirectly. The impact of autonomy and competence support was found to promote emerging adults' intrinsic motivation, which consequently influenced actual physical activity and behaviour.